Manusia Sebagai Makhluk Pedagogik - Ana Fergina; Wahyuddin Naro; Yuspiani Yuspiani (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This article aims to better understand the role of humans as pedagogical creatures according to a review of the Qur'an and educational science. This conceptual paper uses various literature, such as articles, journals, and books, to explore concepts, ideas, and theories of a problem. The study results show that as pedagogical creatures, humans carry out their duties and functions on earth as 'abd Allah and caliph. To optimize their nature, efforts must be made. Education and a conducive environment are said to help develop the potential of humans to become human beings.